The New Corrugation Pattern for Low Pressure Plate Condensers - Tovazhnyanskyy, Leonid Leonidovich; Kapustenko, P. O.; Perevertaylenko, O. Yu.; Arsenyeva, O. P.; Khavin, G. L. (The Italian Association of Chemical Engineering, 2010)
Low pressure and especially vacuum vapours condensation processes are widely used in different industries such as power generation, chemical, biochemical, pharmaceutical, food etc. Plate Heat Exchangers (PHEs) are one of the modern efficient types of heat transfer equipment, but their usage as condensers for low pressure vapour is limited mostly because of relatively high pressure drop of condensing media. To overcome this obstacle the new principle of plate corrugation for low pressure plate-and-frame condensers is proposed. The basic trends on developments of corrugated patterns for low pressure plate condensers were investigated. The principle of channels with variable geometry was selected for new corrugated pattern development. The proposed plate for condenser has the heat transfer area that consists of several corrugated sections along its length. Shape and dimensions of ridges and valleys of corrugations are variable. The corrugations are inclined to plate vertical axis so the ridges of two adjacent plate corrugations are in contact. The channel formed by such plates has the variable cross-section area. The experimental study of heat transfer and pressure drop for channels of such pattern was carried out. The dependencies for film heat transfer and pressure drop were obtained for each channel part formed with adjacent sections of the plates. The obtained results were compared with those for plates which are conventionally used. The advantages of proposed corrugation are discussed. The calculation methods based on obtained results were developed for single-phase flows heat exchange and for condensation of pure vacuum vapours. The recommendations on plate surface synthesis are presented.